Energy-consumption-balanced efficient source-location privacy preserving protocol in WSN - Xiao-guang NIU; Chuan-bo WEI; Ya-lan YAO (Tongxin xuebao)
Considering the conflicts among anonymity, network load and transmission latency for most of the existing event source-location privacy (SLP) in wireless sensor network (WSN).Firstly,the effect of the data mixing and fake packet injec-tion on the privacy and network performance was analyzed. Then, the anonymity-quantified dynamic mix-ring-based source-location anonymity protocol(ADRing)was proposed, ADRing which was designed to achieve source anonymity and balance between network traffic and real event report latency through the dynamic mix-ring based packet confusion and the corresponding sector-based anonymity assess and the radius of non-uniform clusters. The simulation results demonstrate that ADRing is very efficient in balancing energy consumption and transmission latency, and can significantly prolong survival period of the network and ensure security as well as latency to satisfy the packets' requirements.